¿Los síntomas de la histeria de finales del siglo XIX se transformaron en los síntomas de la anorexia de finales del siglo XX? (2015)
The following article is a monographic study based on the hysteria and anorexia. We try to find a relationship between the Symptoms of hysteria in the end of the 20st century and the symptoms of anorexia in the end of the 21st century, taking some of the most respected authors as our guide. We try to identify the hysterical symptoms manifested in the stories written by Freud have changed into the symptoms of actual anorexia becoming the anorexia in hysteria of our time, thinking about the exclusion of the pathology of the diagnostics manuals.